2010
DOI: 10.1177/0300985810378112
|View full text |Cite
|
Sign up to set email alerts
|

Pathology of Inhalational Anthrax Animal Models

Abstract: Anthrax is a lethal disease caused by the bacterium Bacillus anthracis. There are three principal forms of the disease in humanscutaneous, gastrointestinal, and inhalational-depending on the route of exposure. Of these, inhalational anthrax is the most dangerous; it is rapidly fatal; and it has been used as a deadly biological warfare agent in the last decade. Suitable animal models of inhalational anthrax have been utilized to study pathogenesis of disease, investigate bacterial characteristics such as virule… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
87
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 82 publications
(94 citation statements)
references
References 59 publications
5
87
0
Order By: Relevance
“…In contrast to the Moayeri hypoxia study, necropsies from B. anthracis infections show fibrin deposits and vasculitis in several animal models [96]. What is striking is that the bacilli can reach such high numbers in hosts before there are any overt signs of morbidity.…”
Section: Cardiovascular and Endothelial Effectsmentioning
confidence: 70%
See 4 more Smart Citations
“…In contrast to the Moayeri hypoxia study, necropsies from B. anthracis infections show fibrin deposits and vasculitis in several animal models [96]. What is striking is that the bacilli can reach such high numbers in hosts before there are any overt signs of morbidity.…”
Section: Cardiovascular and Endothelial Effectsmentioning
confidence: 70%
“…This peptide-based capsule is atypical from other bacterial capsules, including many of those in Bacillaceae [17,82]. The capsule is considered a major virulence factor, as infection with a capsule deficient strain has drastically reduced mortality in most hosts, yet it remains poorly studied compared to the exotoxin [93][94][95][96]. The capsule is thought to act to prevent phagocytosis, but more recent studies have suggested that the capsule also interacts with the exotoxin to increase virulence [97,98].…”
Section: The Vegetative Bacillimentioning
confidence: 99%
See 3 more Smart Citations